PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN TAMU DI HOTEL PATRA JASA BALI RESORT & VILLAS KUTA- BADUNG - I Ketut Sirna (Majalah Ilmiah Widyacakra, 2019)
In hotel services, satisfaction with guests is the most preferred thing in the hospitality service industry to achieve the maximum target of opinion in a hospitality business. And as a service provider in particular the quality of service to guests is very important. so that your needs and desires can be fulfilled well in maintaining the company's image and avoiding complaining from guests. This study aims to determine the effect of service quality on guest satisfaction at Patra Hotel Jasa Bali Resort & Villas Kuta Badung. This study collected data with questionnaires on 100 respondents. which is then analyzed by using multiple linear regression analysis, using the t test and f. The results showed partially, Tangible (X1) of 2.534, Reliability (X2) of 2.611, Responsiveness (X3) of 2.153, Assurance (X4) of 2.637, Empathy (X5) of 2.102, of Guest Satisfaction (Y) in Hotels Patra Jasa Bali Resort & Villas Kuta Badung and simultaneously the influence of service quality (tangible, reliability, responsiveness, assurance, and empathy) amounted to 35,809 to the quality of service at Hotel Patra Jasa Bali Resort & Villas. Based on the calculation of determination analysis obtained the coefficient of determination of 65.6% means that the contribution of the effect of direct evidence variables, reliability, responsiveness, assurance and empathy to guest satisfaction is 65.5% while the remaining 34.9% is influenced by other variables not examined. Based on the results obtained by researchers, that the Patra Jasa Bali Resort & Villas Hotel has been good in the quality of its services.